2016
DOI: 10.1631/jzus.a1500111
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics analysis of a misaligned rotor-bearing system with squeeze film dampers

Abstract: Abstract:In this paper, a dynamic model is established for a two-stage rotor system connected by a gear coupling and supported on ball bearings with squeeze film dampers (SFDs). The nonlinear dynamic behavior of the rotor system is studied under misalignment fault condition. The meshing force of the gear coupling is calculated considering the deformation of the tooth caused by torque transmission and dynamic vibration. The contact force between the ball and race is computed based on the Hertzian elastic contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 40 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…According to the pervious study [12], it is found that most of the oil film clearances in the contact zone are nearly unchanged, so the central oil film clearance can be used as equivalent. In the case of point-contact, the oil film thickness equation is suitable for the ball bearing:…”
Section: Ball Bearingmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the pervious study [12], it is found that most of the oil film clearances in the contact zone are nearly unchanged, so the central oil film clearance can be used as equivalent. In the case of point-contact, the oil film thickness equation is suitable for the ball bearing:…”
Section: Ball Bearingmentioning
confidence: 99%
“…To examine the rotor model, a group of experimental results [12] under different misalignments are used. The comparison between the simulation and the experiments are given in Table 2 and Fig.…”
Section: Rotor System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars focused on the dynamic characteristics of the rotor system affected by SFD [13][14][15]. Previous work on SFD on a two-disk rotor system with misalignment and the effects of SFD was discussed [16].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of previous work [16], this paper developed a model of bearing which considered both Hertz contact and elastohydrodynamic lubrication. This model was focused on studying the fault characteristics of the rotor system caused by inner race defects.…”
Section: Introductionmentioning
confidence: 99%